Causal Associations Between Sarcopenia and Gestational Diabetes Mellitus - Huang Y; Zhao S; Hong J; Shen L; Wang Z; Wang D (International Journal of Women's Health)
Yihong Huang,1,2,* Shanshan Zhao,1,2,* Jiajun Hong,1,2 Lixia Shen,1,2 Zilian Wang,1,2 Dongyu Wang1,2 1Department of Obstetrics and Gynecology, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of China; 2Guangdong Provincial Clinical Research Center for Obstetrical and Gynecological Diseases, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dongyu Wang; Zilian Wang, Department of Obstetrics and Gynecology, The First Affiliated Hospital of Sun Yat-sen University, No. 58 Zhongshan Er Road, Guangzhou, People’s Republic of China, Email wangdy28@mail.sysu.edu.cn; wangzil@mail.sysu.edu.cnIntroduction: Sarcopenia may affect the onset of gestational diabetes mellitus (GDM). However, the causal relationship between sarcopenia and GDM remains unclear. In this study, we used a bi-directional Mendelian randomization (MR) approach to explore this intricate relationship.Methods: This study utilized data from FinnGen datasets and genome-wide association studies. A bi-directional MR study was conducted. First, a forward MR analysis evaluated the causality of sarcopenia on GDM risk, with sarcopenia-related traits as exposures and GDM as the outcome. Second, in the reverse MR analysis, we assessed whether GDM influenced sarcopenia-related traits. Finally, sensitivity analysis was conducted to assess the robustness of the MR analysis.Results: Forward MR analysis revealed that appendicular lean mass (odds ratio [OR] = 1.2182, 95% confidence interval [CI]: 1.1397– 1.3021, P < 0.0001), right-hand grip strength (OR= 1.4194, 95% CI: 1.0773– 1.8701, P= 0.0128), left-hand grip strength (OR= 1.6064, 95% CI: 1.2829– 2.0115, P < 0.0001), and usual walking pace (OR= 3.3676, 95% CI: 1.8769– 6.0423, P < 0.0001) were associated with an increased risk of GDM. However, according to the reverse MR results, GDM had no causal effect on sarcopenia. No pleiotropy was observed.Conclusion: In summary, sarcopenia had a significant causal influence on GDM, while GDM did not causally affect sarcopenia. Keywords: gestational diabetes mellitus, Mendelian randomization, sarcopenia, appendicular lean mass, hand grip strength, usual walking pace